Cardiovascular manifestations of the emerging dengue pandemic - Yacoub, S; Wertheim, H; Simmons, C; Screaton, G; Wills, B (Nature Publishing Group, 2014)
Dengue is one of the most important emerging viral diseases globally. The majority of symptomatic infections result in a relatively benign disease course. However, a small proportion of patients develop severe clinical manifestations, including bleeding, organ impairment, and endothelial dysfunction with increased capillary permeability causing hypovolaemic shock that can lead to cardiovascular collapse. Evidence is increasing that dengue can also cause myocardial impairment, arrhythmias and, occasionally, fulminant myocarditis. No antiviral agents or vaccines are licensed for dengue, and treatment remains supportive with judicious fluid replacement for patients with severe disease. Defining the role of cardiac dysfunction in the haemodynamic compromise of severe dengue has potentially important management implications. In this Review, we will outline the current understanding of the cardiovascular manifestations of dengue, including myocardial and vascular involvement, and conclude with a discussion of the available therapeutic options and potential future research directions.